Modeling the effects of health care expenditure and economic growth in Nigeria: An econometric analysis - Lasbrey Iheanyi Anochiwa; Eze Obila; Michael Enyoghasim (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
Literature abounds that labor quality, in the form of human capital, clearly contributes significantly to productivity growth, but very few analysts have been interested to locate potential human capital growth outside education. Such interest will help ascertain the effectiveness of public health expenditure on health and the impact of good health to economic growth in Nigeria. This research empirically attempts to analyze health outcome and economic growth; proxied by life expectancy at birth and gross domestic product per-capita respectively using quantitative analysis. To avoid the possibility of encountering simultaneity error, we use the three stage -least -square (3SLS) regression to estimate the result. The result shows simultaneity between health outcome and economic growth. The results equally show that health expenditure is significant in determining health outcome but has no significant relationship with economic growth. As a recommendation government must increase budgetary allocation to the health sector and effectively monitor its utilization.